Effect of Reactive Metakaolin Prepaird by Thermal Shock on Some Mechnical Properties of Self-Compacting Concrete (Journal of University of Babylon for Engineering Sciences, 2019)
Metakaolin is a very active alumino-silicate pozzolan commonly used recently in many applications of concrete. In this research Metakaolin was used in production of self-compaction concrete with (20%) replacement of cement by weight. It was prepared by burning natural kaolin Clays at different temperatures (700, 750 , 850) Co  using thermal shock  method and for periods of time ( 0.5 , 1 , 2 ) hours. Fresh self-compacting concrete (SCC) properties, some of mechanical properties were tested at age (28, 56, 90) day.  The findings demonstrate that the fresh properties of SCC are affect by the change of temperature and duration of calcining slightly, while the compressive strength enhanced with increasing of temperature and duration of calcining. The best result is obtained at degree of 850 Co and one-hour calcining duration, while the strength development at (56 day) age was (15.6%) and at (90 day) age was (26.7%). A better enhancement outcome in flexural strength and ultra-sonic plus velocity were at the same temperature and duration of calcining, the development of modulus of rupture at (56 days) was (7%) and at (90 days) it was (15.5 %), while the ultra-sonic plus velocity reached at the age of (28 days ) (4.52 km\sec).